HEPATITIS C VIRUS (HCV) AWARENESS AMONG MEDICAL STUDENTS IN RAWALPINDI: Hepatitis C Virus (HCV) Awareness - Bashir, Qudsia; Rashid, Amir; Naveed, Abdul Khaliq; Mehboob, Khadija; Razak, Suhail; Shah, Syed Zubair Hussain (Pakistan Armed Forces Medical Journal, 2015)
Objective: To assess HCV awareness level among medical students. Study Design: Cross sectional descriptive study. Place and Duration of Study: The study was conducted at Army Medical College Rawalpindi from March to October 2012. Methodology: A structured questionnaire based cross sectional study was conducted including male and female medical students from 3rd and 4th year of both MBBS and BDS classes. The data was reported in the form of frequencies and percentages of correct answers and p value was calculated for the difference in level of correct answers regarding HCV routes of transmission, between male and female students using chi-square test. Results: Survey showed that male students were more knowledgeable about HCV than females. Regarding possible transmission routes for HCV, it is evident that most of the students knew that main spreading cause is blood products, injection drug users and reuse of syringes as compared to other risks. Misconceptions observed are of significance especially at the level of health care providers as this can hinder their professional duties, interaction with the patient and treatment. Conclusion: Knowledge regarding HCV among medical students is inadequate and it can influence HCV prevalence, treatment and management in society.